Strengthening Civic Education Through Multidisciplinary Collaboration (PKn-Sociology): Examining the Impact of Globalization on National Identity Among Adolescents - Tetep, Tetep; Setiawan, Yayan; ., Hendiyansyah; Sarippudin, Ujang; Sudarmanto, Resty Istiarti; Hardiyanti, Tri Widi; ., Inaiyah Widi; Amelia, Liska; Nurhasanah, Sopia Widi; Suryanto, Rendi Widi (Fakultas Kewirausahaan Universitas Garut, 2025)
This community service program, titled